Pemanfaatan Digital Marketing Bagi Usaha Mikro, Kecil Dan Menengah Di Kedai Cakwei’in Karawang, Jawa Barat - Ari Awaludin; Devina Delta Maharani; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Community Service Partners in this activity are Micro, Smalland Medium Enterprises (MSMEs) in the business of producing and selling culinary in karawang. This MSME has been in Karawang city for more than 30 years. However, the marketing system that used is still very minimal and conventional. Forthis reason, MSMEs need to be given training on the importance of using digital marketing so that the marketing system can be better to achieve the desired targets and can support better sales activities. In addition, MSMEs also provide assistance in creating business accounts in digital media such as Google Business and Instagram, and how to manage this digital media optimally Output fromthis ativity is a Google business and InstagramBusiness account, scientific articlepublished in national journals, and activity reports. The method used is by provide training to create accounts in digital media for the MSME and how to manage it optimally. The results showed thatdigital marketing strategy assistance by Community Service Partners can be followed up with periodic guidance that can be done effectively and optimally in supporting MSME marketing activities to increase sales of MSME businesses